Heritability Estimation in Casuarina Progeny-cum-family Test Plot -1996 - Rao, P. S.; Rao, G. Maheswara; Venkaiah, K.; Satyanarayana, V. V. V. (Indian Forester, 2001)
At Regional Forest Research Centre, Rajahmundry, East Godavari District, Andhra Pradesh the genetic improvement of Casuarina was commenced in 1994 and to date, considerable work under this project has been done, Candidate Plus Trees have been selected and established progeny tests. The progeny test comprises 16 families (16 CPTs) selected in North Coastal districts of Andhra Pradesh. In progeny test, the data was recorded at 24 months age for plant height, girth at ground level, girth at breast height, axis-persistence and straightness which showed great variation among the families. The characters Ggl, Gbh and straightness are showing significance at Pâ‹ O.05 level of significance. The broad sense heritability and genetic advance were calculated for all the parameters recorded and are presented. The interim results of this trial suggests that the further selections can bc made after monitoring the experiments for 3 to 4 years.